Boosting Photoelectrochemical Water Oxidation of Hematite in Acidic Electrolytes by Surface State Modification. Issue 34 (30th July 2019) - Tang, Peng‐Yi; Han, Li‐Juan; Hegner, Franziska Simone; Paciok, Paul; Biset‐Peiró, Martí; Du, Hong‐Chu; Wei, Xian‐Kui; Jin, Lei; Xie, Hai‐Bing; Shi, Qin; Andreu, Teresa; Lira‐Cantú, Mónica; et al.
Abstract: State‐of‐the‐art water‐oxidation catalysts (WOCs) in acidic electrolytes usually contain expensive noble metals such as ruthenium and iridium. However, they too expensive to be implemented broadly in semiconductor photoanodes for photoelectrochemical (PEC) water splitting devices. Here, an Earth‐abundant CoFe Prussian blue analogue (CoFe‐PBA) is incorporated with core–shell Fe2 O3 /Fe2 TiO5 type II heterojunction nanowires as composite photoanodes for PEC water splitting. Those deliver a high photocurrent of 1.25 mA cm −2 at 1.23 V versus reversible reference electrode in acidic electrolytes (pH = 1). The enhancement arises from the synergic behavior between the successive decoration of the hematite surface with nanolayers of Fe2 TiO5 and then, CoFe‐PBA. The underlying physical mechanism of performance enhancement through formation of the Fe2 O3 /Fe2 TiO5 /CoFe‐PBA heterostructure reveals that the surface states' electronic levels of hematite are modified such that an interfacial charge transfer becomes kinetically favorable. These findings open new pathways for the future design of cheap and efficient hematite‐based photoanodes in acidic electrolytes. Abstract : Detailed understanding of the semiconductor/electrolyte interface is critical to further development of photoelectrodes for photoelectrochemical water splitting. It is found that modifying the hematite/electrolyte interface with ultrathin Fe2 TiO5 and CoFe PBA improves the photoelectrochemical water oxidation of hematite photoanodes in acidic electrolytes. The modified hematite/electrolyte interface alters the surface states at hematite photoanodes, and thus improves the surface water oxidation kinetics.